Impact of selected comorbidities on the presentation and management of aortic stenosis - Rudolph, Tanja K; Messika-Zeitoun, David; Frey, Norbert; Thambyrajah, Jeetendra; Serra, Antonio; Schulz, Eberhard; Maly, Jiri; Aiello, Marco; Lloyd, Guy; Bortone, Alessandro Santo; Clerici, Alberto; Delle-Karth, Georg; et al. (Open heart, 2020)
BACKGROUND: Contemporary data regarding the impact of comorbidities on the clinical presentation and management of patients with severe aortic stenosis (AS) are scarce. METHODS: Prospective registry of severe patients with AS across 23 centres in nine European countries. RESULTS: Of the 2171 patients, chronic kidney disease (CKD 27.3%), left ventricular ejection fraction (LVEF) <50% (22.0%), atrial fibrillation (15.9%) and chronic obstructive pulmonary disease (11.4%) were the most prevalent comorbidities (49.3% none, 33.9% one and 16.8% ≥2 of these). The decision to perform aortic valve replacement (AVR) was taken in a comparable proportion (67%, 72% and 69%, in patients with 0, 1 and ≥2 comorbidities; p=0.186). However, the decision for TAVI was more common with more comorbidities (35.4%, 54.0% and 57.0% for no, 1 and ≥2; p<0.001), while the decision for surgical AVR (SAVR) was decreased with increasing comorbidity burden (31.9%, 17.4% and 12.3%; p<0.001). The proportion of patients with planned AVRs that were performed within 3 months was significantly higher in patients with 1 or ≥2 comorbidities than in those without (8.7%, 10.0% and 15.7%; p<0.001). Furthermore, the mean time to AVR was significantly shorter in patients with one (30.5 days) or ≥2 comorbidities (30.8 days) than in those without (35.7 days; p=0.012). Patients with reduced LVEF tended to be offered an AVR more frequently and with a shorter delay while patients with CKD were less frequently treated. CONCLUSIONS: Comorbidities in severe patients with AS affect the presentation and management of patients with severe AS. TAVI was offered more often than SAVR and performed within a shorter time period.
Keywords: klinické rozhodování; tepový objem; Registries; aortální stenóza; Humans; Stroke Volume; funkce levé komory srdeční; registrace; prevalence; Female; rizikové faktory; chirurgická náhrada chlopně; Aged; Time Factors; výsledek terapie; Time-to-Treatment; senioři; komorbidita; lidé; Atrial Fibrillation; chronická renální insuficience; Aortic Valve Stenosis; Europe; Transcatheter Aortic Valve Replacement; časové faktory; transkatetrální implantace aortální chlopně; čas zasáhnout při rozvinutí nemoci; ženské pohlaví; stupeň závažnosti nemoci; Clinical Decision-Making; Comorbidity; Male; aortic valve disease; Treatment Outcome; Aged, 80 and over; chronická obstrukční plicní nemoc; prosthetic heart valves; Severity of Illness Index; Prevalence; senioři nad 80 let; Pulmonary Disease, Chronic Obstructive; Risk Assessment; cardiac surgery; mužské pohlaví; prospektivní studie; Renal Insufficiency, Chronic; Heart Valve Prosthesis Implantation; hodnocení rizik; Evropa; fibrilace síní; Ventricular Function, Left; Risk Factors; Prospective Studies